Optimizing Work Online Services Based Inaportnet To Increase Service On Shipping Arrival at PT Maskapai Pelayaran Pulau Laut Panjang Branch - Retno Indriyati; Baharudiansyah Dwiputra Novarizal (Politeknik Bumi Akpelni, 2019)
This writing aims to find out about Standard Operating Procedure and Service Level Agreement Inaportnet system, from before the ship arrived until the management of ship permit out. In carrying out the ship agency's duties which include ship clearance activities with Inaportnet, it is necessary to have knowledge of Inaportnet application form. Data collection methods used in the writing of Scientific Writing is a method of observation or observation, interview or interview method, literature study method and documentation method. The results of the writing show that online services based on Inaportnet can facilitate the tasks of the users of sea transport services in serving the arrival of ships in the Port of Bandar Lampung. However, there are still obstacles in the application of Inaportnet system such as low quality of service, network interruption on server, lack of utilization of science and technology and complicated application usage procedure. The result of this writing can be concluded that Inaportnet-based online service is a single electronic information service system based on internet to integrate port system of information which nature standard serve ship and goods from all related institution or stakeholder at port.